2021
DOI: 10.1016/j.scitotenv.2020.142016
|View full text |Cite
|
Sign up to set email alerts
|

The microbial ecology of a Mediterranean chlorinated drinking water distribution systems in the city of Valencia (Spain)

Abstract: This is a repository copy of The microbial ecology of a Mediterranean chlorinated drinking water distribution systems in the city of Valencia (Spain).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The difference between the decay times at temperatures of 15 °C and 30 °C was 104 h because the growth and reproduction of microorganisms is generally promoted at higher temperatures, but inhibited at lower temperatures. Previous studies showed that higher temperatures can also accelerate reactions and microbial growth in drinking water distribution systems, 30 and the biofilm activity is reduced at lower or higher temperatures. 31,32 The biofilms on the pipe walls require more DO at higher temperatures, thereby accelerating the attenuation of DO.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between the decay times at temperatures of 15 °C and 30 °C was 104 h because the growth and reproduction of microorganisms is generally promoted at higher temperatures, but inhibited at lower temperatures. Previous studies showed that higher temperatures can also accelerate reactions and microbial growth in drinking water distribution systems, 30 and the biofilm activity is reduced at lower or higher temperatures. 31,32 The biofilms on the pipe walls require more DO at higher temperatures, thereby accelerating the attenuation of DO.…”
Section: Resultsmentioning
confidence: 99%
“…As implied in the previous section, sensory problems with tap water are likely to be caused during the distribution process after flowing out of the water plant, which is more difficult to control. A water quality strategy to maintain the stability of the water quality in the network , or a hydraulic strategy to regulate the flow is recommended to control off-flavors in recent research.…”
Section: Discussion and Future Prospectmentioning
confidence: 99%
“…However, low DNA concentration or any genetic markers have been demonstrated to give high false-negative results, increased false discovery and artefactual results [ 44 , 52 ] that is likely to be the case for sequencing-based studies in chlorinated drinking water [ 29 ]. We found that many reported drinking water microbiome studies from chlorinated systems (including 16s rRNA amplicon sequencing/metabarcoding, metagenomics) [ 20 , 56 64 ] often exclude raw experimental data of extracted DNA concentrations that is crucial to assess the quality of the sequencing results.…”
Section: Discussionmentioning
confidence: 99%